Strength training for arterial hypertension treatment: a systematic review protocol - Tebar, William Rodrigues [UNESP]; Rufino, Jéssica Costa [UNESP]; Cruz Veras, Allice Santos [UNESP]; Correia, Rafael Ribeiro [UNESP]; Teixeira, Giovana Rampazzo [UNESP] (Taylor & Francis, 2021)
Background: Hypertension is one of the most prevalent chronic diseases and a leading cause of mortality worldwide. High blood pressure levels can be modified and controlled through both drug and non-drug treatments, such as physical exercise. However, the effects of strength training on hypertension is still not consensual in the literature. Objectives: The current review aimed to investigate, synthesize, and discuss the effects of strength training for treatment of hypertension in adults. Method: Six electronic databases; MEDLINE (through PubMed), Cochrane Library, EMBASE, Scopus, Lilacs, and the World Health Organization will be searched for randomized controlled trials which investigated a strength training intervention longer than 8 weeks to prevent or treat high blood pressure. The search will be performed in December 2020, by two independent reviewers. Studies published from database inception up to 2020, in English or Portuguese languages, will be included. The PICO question is defined as follows: Patients who have Hypertension; Intervention of strength training treatment; Comparison with patients without strength training or strength training pre- and post-treatment; and Outcome which reports clinical indices (crude number or proportion of variation). The risk of bias will be assessed using the Cochrane tool. The primary outcomes will be whether strength training interventions promote changes in blood pressure and its hypotensive effects. Secondary outcomes will analyze the intervention protocols of strength training on blood pressure, in order to synthesize, discuss, and determine the best type of protocol to be used in hypertension treatment in the adult population. PROSPERO registration number: CRD42020151269.
Keywords: Blood pressure; exercise; hypertension; physical activity; strength training